Racial/ethnic disparities in influenza risk perception and vaccination intention among Pima County residents in Arizona. Issue 7 (30th December 2022) - Mantina, Namoonga M.; Block Ngaybe, Maiya; Johnson, Kerry; Velickovic, Sonja; Magrath, Priscilla; Gerald, Lynn B.; Krupp, Karl; Krauss, Beatrice; Perez-Velez, Carlos M.; Madhivanan, Purnima
ABSTRACT: While influenza cases in Arizona have nearly tripled since 2018, vaccination rates continue to lag. Statewide, Hispanics and African Americans had the lowest vaccination rates despite having higher influenza infection rates than Whites. Given Arizona's racial influenza vaccination disparity and the general increase in vaccination hesitancy due to COVID-19, the purpose of this study was to better understand the influences of seasonal influenza vaccination in Arizona during the COVID-19 pandemic using qualitative methods. Findings from this study revealed that many participants were motivated to get the influenza vaccine to protect their family and close friends. The heightened concern for COVID-19 prompted some Hispanic/Latino focus group discussion participants to consider getting vaccinated. However, many Hispanic/Latino participants also expressed that they stopped getting influenza vaccine due to negative vaccination experiences or concern about sickness following immunization. African American participants primarily discussed receiving the vaccine as part of their routine health visit. Compared to other races, more White participants believed that vaccination was unimportant because they were healthy, and the people they interacted with never got sick. Distinct factors influence risk perception and vaccination intention across different racial/ethnic groups. Effective interventions can account for these factors and be tailored to the target population to maximize vaccination uptake.